PERBEDAAN KECEPATAN DAN KETEPATAN MENJAWAB SOAL DENGAN MENGGUNAKAN APLIKASI WHATSAPP DAN GOOGLE FORM PADA PELAJARAN EKONOMI DI SMK MULTI KARYA MEDAN - Dina Ariska, Rijal (EDUCATE, 2025)
The type of research used is quantitative research. The data collection instrument is a test in the form of an essay of 30 items. The Experimental Technique is used. Where the total population and sample are 18 people as research samples. From the results of the study, the average learning outcomes using the learning model using the Whatsapp Application were 87.7 and using the learning model using the Google Form Application were 86.3. While the results of the t-test calculation obtained the results of the significance level with a = 0.05 and dk = (n1 + n2– 2) = (18 + 18 – 2) = 34, then the results of the t count = 0.03 and t table = 1,734 were obtained from the t distribution table, with t count < t table, thus the hypothesis formulated in this study is: "there is a difference in student learning outcomes using the learning model using the Whatsapp Application and using the Google Form Application in economics lessons for class X students of SMK Multi Karya Medan. The conclusion of this study is (1) The learning outcomes of students who use the learning model using the Whatsapp Application are higher than the learning outcomes of students who use the Google Form Application learning model. (2) There is a difference between the Whatsapp Application Learning Model and the Google Form Application on Student learning outcomes.